Comparative safety of antiepileptic drugs for neurological development in children exposed during pregnancy and breast feeding: a systematic review and network meta-analysis. Issue 7 (20th July 2017) - Veroniki, Areti Angeliki; Rios, Patricia; Cogo, Elise; Straus, Sharon E; Finkelstein, Yaron; Kealey, Ryan; Reynen, Emily; Soobiah, Charlene; Thavorn, Kednapa; Hutton, Brian; Hemmelgarn, Brenda R; Yazdi, Fatemeh; et al.
Abstract : Objectives: Compare the safety of antiepileptic drugs (AEDs) on neurodevelopment of infants/children exposed in utero or during breast feeding. Design and setting: Systematic review and Bayesian random-effects network meta-analysis (NMA). MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials were searched until 27 April 2017. Screening, data abstraction and quality appraisal were completed in duplicate by independent reviewers. Participants: 29 cohort studies including 5100 infants/children. Interventions: Monotherapy and polytherapy AEDs including first-generation (carbamazepine, clobazam, clonazepam, ethosuximide, phenobarbital, phenytoin, primidone, valproate) and newer-generation (gabapentin, lamotrigine, levetiracetam, oxcarbazepine, topiramate, vigabatrin) AEDs. Epileptic women who did not receive AEDs during pregnancy or breast feeding served as the control group. Primary and secondary outcome measures: Cognitive developmental delay and autism/dyspraxia were primary outcomes. Attention-deficit hyperactivity disorder, language delay, neonatal seizures, psychomotor developmental delay and social impairment were secondary outcomes. Results: The NMA on cognitive developmental delay (11 cohort studies, 933 children, 18 treatments) suggested that among all AEDs only valproate was statistically significantly associated with more children experiencing cognitive developmental delay compared with control (OR=7.40, 95% credible interval (CrI) 3.00 to 18.46). The NMA on autism (5 cohort studies, 2551 children, 12 treatments) suggested that oxcarbazepine (OR 13.51, CrI 1.28 to 221.40), valproate (OR 17.29, 95% CrI 2.40 to 217.60), lamotrigine (OR 8.88, CrI 1.28 to 112.00) and lamotrigine+valproate (OR 132.70, CrI 7.41 to 3851.00) were associated with significantly greater odds of developing autism compared with control. The NMA on psychomotor developmental delay (11 cohort studies, 1145 children, 18 treatments) found that valproate (OR 4.16, CrI 2.04 to 8.75) and carbamazepine+phenobarbital+valproate (OR 19.12, CrI 1.49 to 337.50) were associated with significantly greater odds of psychomotor delay compared with control. Conclusions: Valproate alone or combined with another AED is associated with the greatest odds of adverse neurodevelopmental outcomes compared with control. Oxcarbazepine and lamotrigine were associated with increased occurrence of autism. Counselling is advised for women considering pregnancy to tailor the safest regimen. Trial registration number: PROSPERO database (CRD42014008925).